X-ray parametric down-conversion reveals EUV-polariton - Dietrich Krebs; Fridtjof Kerker; Xenia Brockmüller; Christoph J. Sahle; Blanka Detlefs; Simo Huotari; Nina Rohringer; Christina Bömer (Nature Communications)
Abstract Spontaneous parametric down-conversion (PDC) of photons is a gateway into the quantum realm – thoroughly studied in nonlinear optics and ubiquitously used to generate non-classical states of light. Extending PDC from the visible regime towards shorter wavelengths further enables microscopic resolution of electronic structure and quantum-enhanced X-ray detection, but remained challenging due to the process’ inherently low conversion rate. Here, we resolve the full signal cone of non-degenerate down-conversion at X-ray wavelengths and identify imprints of a polariton in the extreme ultraviolet (EUV) regime. We confirm our finding of the EUV-polariton with theoretical simulations and establish that our approach directly images the characteristic anti-crossing of polaritonic dispersion branches. This insight could open a pathway to explore strong-coupling phenomena of EUV-light-matter interaction.